Antibacterial activity of rice bran oil - Arpan, Dey; Praveen, Jain; Ajay, Singh (Recent Research in Science and Technology, 2013)
Edible oils are widely used. These edible oils have unimaginable medicinal and Pharmaceuticals properties. The oils possessing antimicrobial activity can be employed against human pathogens. Investigations into the antimicrobial activities, mode of action and potential uses of oils have regained momentum. There appears to be a revival in the use of traditional approaches for protecting livestock and food substances from pathogens, pest and spoilage in developing countries. The aim of the present investigation is to assess the anti-bacterial activity of the rice bran oil, so that the intake of rice bran oil might promote human health by preventing bacterial pathogenesis. The bacterial cultures are supplied with rice bran oil (commercially available in the market) and culture conditions are maintained as the normal protocol. The studies reveal antibacterial effect. And inhibition is of permanent nature as petridishes are not found to be infected with any other colony for 5 continuous days.